2021
DOI: 10.1111/1750-3841.15827
|View full text |Cite
|
Sign up to set email alerts
|

Novel alternative for controlling enzymatic browning: Catalase and its application in fresh‐cut potatoes

Abstract: Surface browning is a vital phenomenon that adversely reduces the quality of fresh-cut potatoes. Although many anti-browning methods have been explored, it is unclear whether exogenous catalase (CAT) treatment influences the enzymatic browning. Our results showed that 0.05% CAT immersion for 5 min alleviated browning during cold storage (4 • C, 8 days), which was accompanied by a higher lightness and lower redness; additionally, lower H 2 O 2 and O 2 ⋅contents were found. The activities of CAT, ascorbate perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Interestingly, the pro-oxidant activity of polyphenol was found to enhance antioxidant capacity in human cells ( Tedesco et al, 2021 ). Moreover, antioxidants such as CAT, ascorbic acid, and GSH can efficiently suppress enzymatic browning in fruit and vegetables after harvest ( Qiao et al, 2021 , Sikora and Świeca, 2018 , Wu, 2014 ). Thus, the curcumin-induced inhibition of enzymatic browning may be attributed to its own ability to enhance antioxidant capacity, leading us to question whether curcumin improved the antioxidant capacity of stored soybean sprouts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the pro-oxidant activity of polyphenol was found to enhance antioxidant capacity in human cells ( Tedesco et al, 2021 ). Moreover, antioxidants such as CAT, ascorbic acid, and GSH can efficiently suppress enzymatic browning in fruit and vegetables after harvest ( Qiao et al, 2021 , Sikora and Świeca, 2018 , Wu, 2014 ). Thus, the curcumin-induced inhibition of enzymatic browning may be attributed to its own ability to enhance antioxidant capacity, leading us to question whether curcumin improved the antioxidant capacity of stored soybean sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…is a key enzyme in polyphenol biosynthesis and is also involved in enzymatic browning ( Tomás-Barberán & Espín, 2001 ). Many methods have been developed to inhibit enzymatic browning ( Qiao et al, 2021 , Sikora and Świeca, 2018 ). However, no studies have revealed the potential roles of curcumin in modulating enzymatic browning in fruit and vegetables during storage.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, fresh-cut potatoes were soaked in 0.05% CAT for 5 min and stored at 4 • C for 8 days. The result showed that the H 2 O 2 and O 2− content was significantly lower than in the control [43]. Taro soaked samples in citronella hydrosol (CH) or rose hydrosol (RH) for 30 min, and these were then packed in plastic bags and stored at 4 • C for 12 days.…”
Section: Discussionmentioning
confidence: 99%
“…Potatoes are particularly popular among customers due to their high mineral, dietary fiber, and other nutrient content, as well as their convenient food preparation [ 8 , 9 , 10 ]. However, due to the mechanical tissue damage during the fresh-cutting process, they become prone to accelerated enzymatic browning [ 11 ].…”
Section: Introductionmentioning
confidence: 99%